2010
DOI: 10.1002/sia.3464
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and structural properties of PbSe nanomaterial

Abstract: Lead selenide nanostrucured material was prepared by hydrothermal method. 50 mg of PEG and 2.4 g of NaOH were added to 50 ml of deionized water, then 1 mM each of NaSeO3 and PbAc were added to the solution. 10 ml of hydrazine hydrate was added to the solution and transferred into a Teflon-lined autoclave. The reactants were heated for 9, 10 and 11 h. This process was repeated twice the prementioned concentration. X-ray diffraction, scanning electron microscopy and energy dispersive X-ray analyses were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Such a study will be useful to identify clearly the substrate temperature induced changes in physical properties of thermal evaporated PbSe films (using pre-synthesized PbSe nanocrystalline powders) for any technological applications. As mentioned above, the size and shape of the PbSe nanoparticles play an important role in the physical properties, such as structural, morphology, optical bandgap and nonlinear optical properties [24]. It can be pointed out that the ethylene Contents lists available at SciVerse ScienceDirect journal homepage: www.elsevier.com/locate/jcrysgro diamine tetra acetic acid (EDTA) is a strong chelating agent, to enhance the stable complexes between metal ions and to dissociate at low rate.…”
Section: Introductionmentioning
confidence: 98%
“…Such a study will be useful to identify clearly the substrate temperature induced changes in physical properties of thermal evaporated PbSe films (using pre-synthesized PbSe nanocrystalline powders) for any technological applications. As mentioned above, the size and shape of the PbSe nanoparticles play an important role in the physical properties, such as structural, morphology, optical bandgap and nonlinear optical properties [24]. It can be pointed out that the ethylene Contents lists available at SciVerse ScienceDirect journal homepage: www.elsevier.com/locate/jcrysgro diamine tetra acetic acid (EDTA) is a strong chelating agent, to enhance the stable complexes between metal ions and to dissociate at low rate.…”
Section: Introductionmentioning
confidence: 98%
“…1,3,9 These approaches yield QDs capped with organic (hydrophobic) ligands that are not suitable for biological applications. Other non-aqueous syntheses reported for PbSe QDs involve the use of a microwave-assisted polyol process, 10 a hydrothermal process, 11 and a solvothermal synthesis using octadecylamine. 12 In these methods the final products are not only insoluble in water, but also the fabrication involves the use of toxic solvents that are not desirable for environmental and biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Wang et al [12] showed that the source materials and reaction temperature play important role in forming objective products and controlling their morphologies. In our previous report, face-open nanocubes of PbSe have been prepared by hydrothermal method [13]. It has been found that the morphology of the particles is influenced by the reaction time.…”
Section: Introductionmentioning
confidence: 99%